THE GROWTH OF LOANS GRANTED TO INDIVIDUALS IN UZBEKISTAN AND ITS UNDERLYING REASONS (E Global Congress, 2025)
Nowadays, the stable and sustainable development of the economy is directly linked to the effective and balanced functioning of the country’s financial system. In particular, the growth in both the volume and quality of loans issued by commercial banks is a crucial factor for the qualitative improvement of economic processes, and the expansion of production and consumption sectors. The growing share of loans granted to individuals within the credit portfolio indicates that the population is actively using financial services, reflecting the expansion of their financial needs and capabilities. This, in turn, is associated with growing public trust in the banking system and the implementation of modern methods of digitalization and service delivery.